Physical Quality Responses of Cocoa Beans to Inclusion and Exclusion of Placenta and Varied Fermentation Periods - , J. Amponsah; , P. Kumah; , P. K. Tandoh (Archives of Current Research International, 2019)
Ghana’s premium quality cocoa could be sustained by purging off foreign matter introduced somewhat by placenta mixed with extracted cocoa beans. This study thus examined the effect of placenta and varied fermentation periods on physical quality characteristics of cocoa beans. A field and laboratory studies were done at the Department of Horticulture and Pharmacy, KNUST Kumasi. Experimental design for laboratory work was 2×5 factorial of placenta inclusion or exclusion and varied fermentation days in CRD and replicated three times. Cut test revealed that cocoa beans without placenta were totally clean. Also, the longer the fermentation days with placenta the more chaff content. Longer drying time resulted in the formation of more purple beans while those beans fermented for over six days produced the highest germinated beans. It was concluded that for premium quality cocoa beans, fermentation should be done for, at least, six days without placenta since that improved the physical attributes of the cocoa beans.